Anticancer potential of bioactive 16-methylheptadecanoic acid methyl ester derived from marine Trichoderma - Saravanakumar, Kandasamy; Vivek, Raju; Boopathy, Natarajan Sithranga; Yaqian, Li; Kathiresan, Kandasamy; Chen, Jie (Journal of Applied Biomedicine, 2015)
The present work aimed at purifying the intracellular fungal metabolites, such as 16-methylheptadecanoic acid methyl ester (HDA) and 9,12-octadecadienoic acid (ODA) from marine Trichoderma, Hypocrea lixii TSK8, Hypocrea rufa SKS2 respectively, and investigating their anticancer and antioxidant effects. The two fungal metabolites were tested against two human cancer cell lines, namely oral cancer (KB) and skin carcinoma (A431) by using MTT assay. The inhibitory concentrations (IC50) against KB oral cancer cells were found to be 18.75 ± 0.12 μg/mL for HDA and 75.50 ± 0.42 μg/mL for ODA. Whereas IC50 values of HDA and ODA against A431 were found 37.5 ± 0.42 μg/mL and 72.89 ± 0.15 μg/mL, respectively. In addition, the down-regulation of heat shock protein 90 kDa (HSP90) was confirmed by using SDS-PAGE and Western blot analysis. The effect of HDA induced apoptosis via ROS-dependent internucleosomal DNA fragmentation was confirmed by AGE analysis. We further evaluated the in vivo anti-skin cancer activity of HDA in Swiss albino mice induced with skin cancer by 7,12-dimethylbenz(a)anthracene (DMBA) and croton oil (CO). The in vivo hematological, biochemical and histopathological results revealed that the fungal metabolite HDA was a highly potent anticancer compound against the skin cancer.
Keywords: Animals; Statistics as Topic; apoptóza; Antioxidants; oxidační stres; statistika jako téma; Cell Line, Tumor; houby; Apoptosis; DNA Fragmentation; fragmentace DNA; methyl ester 16-methylheptadekanové kyseliny (HDA) a 9, 12-oktodekanové kyseliny (ODA); HSP90 Heat-Shock Proteins; Oxidative Stress; lidé; Antineoplastic Agents; Mice; protinádorové látky; Trichoderma; myši; Decanoic Acids; nádory kůže; Fungi; proteiny tepelného šoku HSP90; modely nemocí na zvířatech; Skin Neoplasms; kyseliny dekanové; antioxidancia; Disease Models, Animal; zvířata; nádorové buněčné linie; Humans